409 Evaluation of Advanced Bimanual Skills in Novices Using the Wrist-Like FlexDex™ Articulating Laparoscopic Needle Holder in 2D and 3D Vision: A Randomised Trial. (19th August 2022) - Farzaneh, SB; Motahariasl, N; Motahariasl, S; Kokotkin, I; Sousi, S; Zargaran, A; Zargaran, D; Patel, B
Abstract: Aim: The aim of this study was to evaluate the novice performance of advanced bimanual laparoscopic skills using the articulating FlexDex™ laparoscopic needle holder in two-dimensional (2D) and three-dimensional (3D) visual systems. Method: In this prospective randomised trial, novices (n=40) without laparoscopic experience were recruited from a university cohort and randomised into two groups, which used the FlexDex™ and 2D or the FlexDex™ and 3D. Both groups performed 10 repetitions of a validated assessment task. Times taken and error rates were measured, and assessments were made based on completion times, error rates and learning curves. Results: The intervention group that used FlexDex™ and 3D visual output completed 10 attempts of the standardised laparoscopic task quicker than the control group that used FlexDex™ with standard 2D visual output (268 seconds vs 415 seconds taken for the first three attempts and 176 seconds vs 283 seconds taken for the last three attempts, respectively). Moreover, each attempt was completed faster by the intervention group compared to the control group. The difference in average time for the first three and last three attempts reached statistical significance (P < 0.001). Conclusion: Combination of 3D visual systems and the FlexDex™ laparoscopic needle holder resulted in superior task performance speed, leading to shorter completion times and quicker learning effect. Although the 3D group demonstrated lower mean error rates, it did not reach statistical significance.